2007
DOI: 10.1175/mwr3370.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 10-m Wind Forecasts from a Regional Area Model and QuikSCAT Scatterometer Wind Observations over the Mediterranean Sea

Abstract: Surface wind forecasts from a limited-area model [the Quadrics Bologna Limited-Area Model (QBOLAM)] covering the entire Mediterranean area at 0.1° grid spacing are verified against Quick Scatterometer (QuikSCAT) wind observations. Only forecasts within the first 24 h in coincidence with satellite overpasses are used. Two years of data, from 1 October 2000 to 31 October 2002, have been considered, allowing for an adequate statistical assessment under different wind conditions. This has been carried out by analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 37 publications
5
48
0
Order By: Relevance
“…Accadia et al (2007) and Ruti et al (2008) found QuikSCAT to show higher wind speeds than observations from two buoys in the Gulf of Lion area. Therefore, part of the simulation bias could be explained by an overestimation of wind speed by QuikSCAT.…”
Section: Effects Over the Mediterranean Seamentioning
confidence: 92%
See 1 more Smart Citation
“…Accadia et al (2007) and Ruti et al (2008) found QuikSCAT to show higher wind speeds than observations from two buoys in the Gulf of Lion area. Therefore, part of the simulation bias could be explained by an overestimation of wind speed by QuikSCAT.…”
Section: Effects Over the Mediterranean Seamentioning
confidence: 92%
“…QuikSCAT has been used for wind speed analysis in the Mediterranean (e.g., Accadia et al 2007;Ruti et al 2008), as well as in many other regions (Dorman et al 2013;Risien and Chelton 2006). QuikSCAT data have been validated with buoy data in the Gulf of Lion for the period 2000(Accadia et al 2007Ruti et al 2008), showing a bias of about 0.4-0.9 m/s, and an RMSE of about 1.5 m/s. Ruti et al (2008) found the bias of QuikSCAT compared to buoys to be higher for high wind speeds.…”
Section: Quikscat Data Setmentioning
confidence: 99%
“…The interpolation method is pure Laplacian, to avoid excessive data smoothing: it has been demonstrated not to change the wind speed and direction statistics (Accadia et al, 2007). LAMs winds have been mapped to the same grid with the nearest neighbour algorithm.…”
Section: Temporal and Spatial Collocationmentioning
confidence: 99%
“…Accadia et al (2007) analysed the seasonal fields of several statistics parameters, using two years of QuikSCAT L2B 25 km observations and the wind field forecasts produced by the Quadrics Bologna Limited-Area Model (QBOLAM) over the Mediterranean Sea on a 0.1…”
Section: Introductionmentioning
confidence: 99%
“…The first point has been investigated in a systematic comparison of QBOLAM 10 m winds against scatterometer observations (Accadia et al, 2007). It was found that in open sea regions the meteorological model underestimates wind strength from about 0.5 m s −1 in spring and summer to 1.0 m s −1 in winter.…”
Section: Objective Verification Of the System And Applicationsmentioning
confidence: 99%